Public Information, Relative Overconfidence, and Capital Flows - Balakrishnan, Karthik; Bernard, Darren; Rennekamp, Kristina M.; Steenhoven, Blake (Journal of Accounting Research, 2025)
ABSTRACT Capital flows increase in response to new public information. Conventional explanations typically conclude that this reflects a rational response to reduced risk. However, investors may also be overconfident in their ability to benefit from new information, even when it is publicly available and does not provide a relative advantage. We exploit two complementary settings to examine how this “better‐than‐average” mechanism affects capital flows. Archival evidence from horse race betting markets shows capital flows increase following the public provision of a summary measure of horse performance, even though more total parimutuel wagering necessarily implies a greater wealth transfer from bettors to tracks. A controlled lab experiment provides direct causal evidence of our proposed mechanism. Combined, our results suggest that new public information can increase capital flows due to investors’ overconfidence in their ability to benefit from information relative to others. Our findings inform regulators seeking to understand the consequences of expanding the public information available to individual investors.